Single‐Electron Transfer Reactions Enabled by N‐Heterocyclic Carbene Organocatalysis - Li, Qing‐Zhu; Zeng, Rong; Han, Bo; Li, Jun‐Long (Chemistry : a European journal, 2021)
Over the past decades, N‐heterocyclic carbene (NHC) organocatalysis has undergone a flourish of development on the basis of closed‐shell reaction paths. By contrast, the emerging area of single‐electron transfer (SET) reactions enabled by NHC catalysis still remain underdeveloped, but offer plenty of opportunities to develop new catalytic modes and useful synthetic methods. A number of interesting transformations were triggered by the SET process from the electron‐rich Breslow intermediates to various single‐electron acceptors. In additions, recent studies revealed that the Breslow radical cations could also be generated by single‐electron reduction of the electron‐deficient acyl azolium intermediates. These discoveries open a new avenue for NHC organocatalysis to harness radical reactions. The present review will focus on the exciting advancements in the dynamic area of radical NHC organocatalysis. NHC organocatalysis: The development of N‐heterocyclic carbene (NHC) organocatalysis presents new opportunities in radical reactions. The Breslow intermediate‐based radical cations, which could be generated through single‐electron oxidation or reduction, enabled a series of novel radical transformations. These advancements greatly extend the synthetic potential of N‐heterocyclic carbene catalysis.